2015
DOI: 10.1002/app.43316
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polymer matrix on the performance of pressure‐sensitive paint comprising 5,10,15,20‐tetrakis(pentafluorophenyl)porphinato platinum(II) and poly(1,1,1,3,3,3‐hexafluoroisopropyl‐cotert‐butyl methacrylates)

Abstract: Copolymers of 1,1,1,3,3,3-hexafluoroisopropyl methacrylate (HFIPM) and tert-butyl methacrylate (TBM) were prepared by conventional radical copolymerization as a novel binders for pressure-sensitive paints (PSP). The monomer reactivity ratios r HFIPM and r TBM were determined as 0.45 and 0.67, respectively. The glass transition temperature of the copolymers increased from 77 to 1268C with increasing mole fraction of TBM units in the copolymer. The PSP were formed by combining the resulting copolymers and 5,10,1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Obata et al. reported that the temperature sensitivity of poly­( tert -butyl methacrylate) ( T g ∼ 126 °C) was −1.01%/°C . In this work, S T of F1a ( T g ∼ 149 °C) was −0.63%/°C.…”
Section: Resultssupporting
confidence: 48%
See 4 more Smart Citations
“…Obata et al. reported that the temperature sensitivity of poly­( tert -butyl methacrylate) ( T g ∼ 126 °C) was −1.01%/°C . In this work, S T of F1a ( T g ∼ 149 °C) was −0.63%/°C.…”
Section: Resultssupporting
confidence: 48%
“…S T s of F1a , F2 , and F3 were −0.63, −0.61, and −0.92%/°C, respectively. Compared with F3 ( T g ∼ 103 °C), the high glass transition temperature ( T g ) could decrease the temperature dependence, ,, so that luminescent intensities of F1a and F2 were less affected by temperature. Obata et al.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations